Calculating Required Purification Effort to Turn Source Water Into Drinking Water Using an Adapted CCME Water Quality Index - André van denDoel; Geert H. vanKollenburg; Thomas D. N. vanRemmen; Joanne A. deJonge; Geert J. Postma; Gerjen H. Tinnevelt; Gerard J. Stroomberg; Lutgarde M. C. Buydens; Jeroen J. Jansen (Water Resources Research, 2023)
Abstract The 2000 European Union Water Framework Directive (WFD) states that “Member States shall ensure the necessary protection for the bodies of water identified with the aim of avoiding deterioration in their quality in order to reduce the level of purification treatment required in the production of drinking water.” However, it does not specify how to evaluate or quantify this level of purification treatment. We propose a novel water quality index (WQI) to quantify the level of purification treatment required to prepare drinking water from source water. It is based on the WQI of the Canadian Council of Ministers of the Environment (CCME WQI). Our WQI compares measured contaminant concentrations in source water to drinking water guidelines and any exceedance is weighted by a measure of the resilience of that contaminant to the treatment processes, which is not possible in the CCME WQI. Furthermore, it accommodates for varying sampling frequencies that are characteristic of the ongoing monitoring program. These adaptations make our index robust and sensitive to relevant changes in source water quality. We calculated index scores for source water from the Rhine and the Meuse and found no general decrease in required purification treatment levels since the introduction of the WFD.